The influence of compressive gear on maximal load lifted in competitive powerlifting. - Wilk, Michał; Krzysztofik, Michał; Bialas, Marcin (Biology of Sport, 2020)
The competition in powerlifting has been divided into two divisions, with gear equipment (EQ) and without gear equipment (RAW). When competing in the EQ division, additional supportive gear can be worn by the athletes, while in the RAW division such gear is not allowed. The aim of the study was to compare the results of the RAW and EQ powerlifting divisions based on the results of world championships and current world records. One-hundred and twenty powerlifters (63 men, 57 women) were included to the analysis. Post hoc analysis for the results of men’s world championships indicated significantly higher results of the barbell squat (SQ; p < 0.001; ES = 1.31), bench press (BP; p < 0.001; ES = 1.27) and deadlift (DL; p < 0.001; ES = 0.37) for EQ compared to the RAW division. Post hoc analysis for the results of women’s world championships indicated significantly higher results of the SQ (p < 0.001; ES = 1.31), BP (p < 0.001; ES = 1.13) and DL (p < 0.001; ES = 0.71) for the EQ compared to the RAW division. Post hoc analysis for men’s world record indicated significantly higher results in the SQ (p < 0.001; ES = 1.32) and BP (p < 0.001; ES = 1.24) for the EQ compared to the RAW division. Furthermore, there were no significant differences in the results of world records in the DL (p = 0.901; ES = 0.26) between the EQ and RAW divisions. Post hoc analysis for women’s world records indicated significantly higher results in the SQ (p < 0.001; ES = 1.22) and BP (p < 0.001; ES = 1.99) for the EQ compared to RAW division. The main finding of the study was that supportive gear increases maximal load lifted during powerlifting competition.